Avaliação da qualidade do camarão litopenaeus vannamei (boone, 1931) armazenado sob efeito do congelamento associado ao uso do sorbato de potássio - Oliveira, Genilson Batista de (2016)
The search for products that supply more which satiety the persons, it is doing so that the man explores sea foods as fountain of alternative and healthy food. Among several fish sorts, the shrimp is gaining emphasis, due to his composition nutricional and the beneficial effects to the health. But because of being a very perishable food, he are some methods of conservation investigated with the objective to extend his life of shelf, in this work, there was checked the job of additive ones associated to the use of low temperatures. The samples were obtained of a local enterprise, UFPB conditioned and transported to the Center of Technology and of Regional Development-. The products were prepared from whole shrimps and subsequently, subjected to 10 different treatments: T1 and T6 - without additive (control), T2 and T7 - solution of sorbato of potassium to 0,1 %, T3 and T8 - solution of sorbato of potassium to 0,3 %, T4 and T9 - mixes (sorbato of potassium, eritorbato of sodium and chloride of sodium) to 0,1 % and T5 and T10 - it mixes (sorbato of potassium, eritorbato of sodium and chloride of sodium to 0,3 %). The samples of T1, T2, T3, T4 and T5 were subjected to the slow freezing (freezer) temperature of-18°C and the samples T6, T7, T8, T9 T10 were subjected to quick freezing (tunnel of freezing) temperature of-34°C and next they were stored (-18 °C) by a period of 60 days of evaluation. Physical and chemical analyses such as took place pH, water activity, profit in the cooking, capacity of water retention, texture, color, total volatile bases and reactive substances to the acid tiobarbitúrico and microbiological analyses in the times 0 and 60 days. it is possible to end that the effect of the sorbato of potassium associated to low temperatures maintained the quality of the cultivated shrimp, when values are maintained inside the standards demanded by the legislation, when equated to that of the literature..